Redução do desequilíbrio de tensão por meio do controle de componentes de sequência negativa em inversores conectados à rede de distribuição - Conzatti, Nauana del Castanhel (2020)
In Brazil, distribution utilitiesfollow the requirement established by Procedures for Distribution of Electric Energy in the National Electric System, which divides the power quality between product, service, and complaints handling. This dissertation is contextualized in the application of distributed energy resources based on inverters to improve the quality of the product and service. The voltage unbalance affects consumers, distribution utilities and is one of the parameters used to evaluate the product quality. Thus, the main contribution of this work is the Perturb and Observe Factor of Unbalance control structure, implemented in a voltage source inverter to inject specified three-phase powers and reduces the voltage unbalance at the point of common coupling during connected operation. Regarding the quality of service, the improvement of continuity indicators is achieved when a control structure is implemented in the same device to sustain voltage and frequency in specific values and reduce voltage unbalance during isolated and islanded operations. It is used the control of the positive and negative sequence components based on Fortescue Theorem to achieve the mentioned objectives. The implemented structures are evaluated individually with simulations under different scenarios of load demand. It is used the IEEE 34 nodes test feeder modeled in the Alternative Transients Program. The results confirm the effectiveness of the implemented control structures. In different scenarios of parallel operation, the device was able to reduce the voltage unbalance in the point of common coupling and inject the specified three-phase powers. Additionally, during isolated and islanded operations, the inverter maintains the voltage and frequency in specified values during balanced and unbalanced load variations.